Correlational design: health and academic performance in university students - Cortez Gutiérrez, Hernán Óscar; Cortez Gutiérrez, Milton Milcíades (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
A relationship has been determined between professional performance (grades) and fluctuations in joint pain in university students. There are significant differences between the means of joint pain with a Willcoxon statistic of -3.6 and significance of 0. Likewise, a correlation of the grades and fluctuations in joint pain has been obtained, a Rho Spearman of -0.433 and p value of 0.057. The Ruffier index level impacts the averages of university students' grades according to the Kruskal-Wallis statistic.